Dislocation Dynamics During Plastic Deformation - Messerschmidt, Ulrich; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
The book gives an overview of the dynamic behavior of dislocations and its relation to plastic deformation. It introduces the general properties of dislocations and treats the dislocation dynamics in some detail. Finally, examples are described of the processes in different classes of materials, i.e. semiconductors, ceramics, metals, intermetallic materials, and quasicrystals. The processes are illustrated by many electron micrographs of dislocations under stress and by video clips taken during in situ straining experiments in a high-voltage electron microscope showing moving dislocations. Thus, the users of the book also obtain an immediate impression and understanding of dislocation dynamics.
General Properties of Dislocation Motion -- Experimental Methods -- Properties of Dislocations -- Dislocation Motion -- Dislocation Kinetics, Work-Hardening, and Recovery -- Dislocation Motion in Particular Materials -- Semiconductors -- Ceramic Single Crystals -- Metallic Alloys -- Intermetallic Alloys -- Quasicrystals -- Conclusion.
Keywords: Physics; Crystallography; Engineering; Materials; Physics; Crystallography; Condensed Matter Physics; Structural Materials; Engineering, general